Variations of MicroRNAs in Human Placentas and Plasma From Preeclamptic Pregnancy - Xu, Peng; Zhao, Yangyu; Liu, Ming; Wang, Yongqing; Wang, Hao; Li, Yu-xia; Zhu, Xiaoming; Yao, Yuanqing; Wang, Haibin; Qiao, Jie; Ji, Lei; Wang, Yan-ling (Hypertension (Dallas, Tex. 1979), 2014)
Preeclampsia is a major cause of maternal and fetal mortality and morbidity worldwide. The differential expression of several microRNAs (miRNAs) has been found in preeclamptic placentas. However, great conflict exists regarding this aspect, and detailed examinations have largely been lacking of miRNA profiles in different parts of the placenta and in maternal plasma of women with this disorder. In this study, a total of 9 downregulated miRNAs (miR-195, miR-223, miR-218, miR-17, miR-18a, miR-19b1, miR-92a1, miR-379, and miR-411) and 7 upregulated miRNAs (miR-210, miR-30a-3p, miR-518b, miR-524, miR-17-3p, miR-151, and miR-193b) were identified in severe preeclampsia (sPE) placentas when compared with normal pregnant controls. In addition, sampling position in the chorionic or basal plate of placenta led to evident variations in differential miRNAs of sPE placentas. In a prospective pregnant cohort, we found that the circulating levels of 3 members of miR-17-92 cluster (ie, miR-18a, miR-19b1, and miR-92a1) were significantly lower, whereas that of miR-210 was higher in sPE patients than those in normal controls at gestational weeks 15 to 18 and at term. The results of in situ hybridization revealed the localization of miR-18a, miR-92a1, and miR-210 in various subtypes of placental trophoblasts and endothelial cells. In human trophoblast cell line, HTR8/SVneo cells, miR-18a could promote trophoblast cell invasion via targeting and suppressing Smad2 expression. This study provides fundamental evidences for exploring the roles of miRNAs in the pathogenesis of preeclampsia.